2008
DOI: 10.1016/j.abb.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of metabolic defects of yeast isocitrate dehydrogenase and aconitase mutants by loss of citrate synthase

Abstract: Yeast mutants lacking mitochondrial NAD + -specific isocitrate dehydrogenase (idhΔ) or aconitase (aco1 Δ) were found to share several growth phenotypes as well as patterns of specific protein expression that differed from the parental strain. These shared properties of idhΔ and aco1 Δ strains were eliminated or moderated by co-disruption of the CIT1 gene encoding mitochondrial citrate synthase. Gas chromatography/mass spectrometry analyses indicated a particularly dramatic increase in cellular citrate levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Metabolite Analyses-Methods for preparation of whole cell extracts and derivatization for metabolite analyses using gas chromatography/mass spectrometry were previously described in detail (2). Briefly, cells were cultured in YP galactose medium to A 600 nm Х 2.0, and growth was stopped by addition of 100 g/ml of cycloheximide and 40 mM sodium azide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolite Analyses-Methods for preparation of whole cell extracts and derivatization for metabolite analyses using gas chromatography/mass spectrometry were previously described in detail (2). Briefly, cells were cultured in YP galactose medium to A 600 nm Х 2.0, and growth was stopped by addition of 100 g/ml of cycloheximide and 40 mM sodium azide.…”
Section: Methodsmentioning
confidence: 99%
“…This extraction procedure and subsequent derivatization methods were empirically determined to permit reproducible and quantitative analyses of TCA cycle metabolites and related amino acids. Concentrations of denatured proteins in cell extracts were determined using a modified Bradford assay (22) following solubilization of the proteins as previously described (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of intracellular citrate is deleterious in a number of ways, which include chelation of divalent cations and acidification of the intracellular milieu (24).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that ⌬icd and ⌬aco1 mutants of Saccharomyces cerevisiae share several growth phenotypes, for example, poor growth on glycerol, an inability to grow with acetate as the sole carbon source, or a propensity to generate petite segregants, which can be complemented or at least moderated by the codisruption of cit1 coding for mitochondrial citrate synthase (17,37,45).…”
Section: Vol 193 2011 Inactivation Of Citrate Synthase In Aconitasementioning
confidence: 99%